Effects of Pyrolysis Temperature of Macroalgal Biomass on the Structure and Mechanical Properties of Produced Biochar - Brandon Lou; Mallory Parker; Eleftheria Roumeli (BioResources)
Biochars, produced via pyrolysis, are gaining attention in applications ranging from soil amendments to energy storage and environmental remediation. While lignocellulosic biochars from woody biomass are well studied, algal biochars remain comparatively overlooked despite offering diverse organic and inorganic content that may broaden their applications. This study investigates how pyrolysis temperature and oxidative pretreatment affect the structure and properties of biochars derived from two macroalgae, Ulva expansa and Sargassum sp., under various pyrolysis conditions (500 to 900 °C). Using Raman spectroscopy, X-ray photoelectron spectroscopy, X-ray diffraction, scanning electron microscopy, and nanoindentation, it was found that the C-O and C-N surface functional groups decreased in Ulva but the C=O and C-O-C groups increased in Sargassum upon pyrolysis. The reduced modulus ranged between 2.6 to 7.9 GPa and was governed by pyrolytic carbon content and inorganic composition. Of these two factors, the amount and type of pyrolytic carbon were determined by the heating conditions, with oxidation at 200 °C generally preserving more carbon than oxidation at 300 °C. Meanwhile, the final pyrolysis temperature dictated residual carbon content, salt formation, and carbonation. These findings highlight the potential for tailored pyrolysis to produce algal biochars with customizable structures and properties, enabling environmental and industrial applications such as carbon sequestration, filtration, and energy storage.